PENGELOLAAN DESA WISATA UNTUK MENJADIKAN DESA KOLEANG KABUPATEN BOGOR SEBAGAI DESA WISATA UNGGUL - Ardiansyah, Imam; Krisnadi, Antonius Rizki; Iskandar, Hari; Natalia, Dessy; Facrureza, Dewanta; Rosanto, Stephanie; Vishnuvardhana, Vishnuvardhana; Hema, Lamtiar; Djunaid, Ika Suryono; Susanto, Prayogo; Dewantara, Yudhiet Fajar (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program was conducted in Koleang Tourism Village, Bogor Regency, with the aim of enhancing the management of the village as a tourist destination. The main objective of this activity was to improve the capacity and skills of local residents in harnessing tourism potential, enabling Koleang Village to develop into a leading tourist village. The methods used included training, mentoring, and workshops involving various stakeholders such as village authorities, local business operators, and the general community. The results of this program demonstrated an increase in residents' understanding and skills in marketing, service, facility management, and tourism product development. Additionally, the program successfully fostered better collaboration between the community and related parties in the development of the tourism village. Consequently, Koleang Village is expected to become a more attractive and competitive tourist destination, ultimately enhancing the local community's welfare